2021
DOI: 10.37934/arfmts.81.1.8898
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Microcrystalline Cellulose from Oil Palm Empty Fruit Bunch Fibre Using Steam-Assisted Acid Hydrolysis

Abstract: The isolation of microcrystalline cellulose (MCC) from empty fruit bunch fibre (EFB-fibre) using acid hydrolysis through steam treatment (autoclave) followed by ultrasonication has been successfully established. The important parameter studied was the concentration of sulphuric acid (5%, 15% and 25%) at variable fixed reaction time and temperature. The resulting MCC was characterized using FTIR, TGA, XRD and SEM. FTIR transmission at 1163 cm-1 confirmed that the structure of cellulose was retained after underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The preparation of microcrystalline cellulose (MCC) was carried out using published procedure of Ismail et al, [19]. Acid hydrolysis process of MCC was conducted with several concentrations of sulphuric acid (5%, 15%, and 25%).…”
Section: Preparation Of Microcrystalline Cellulosementioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of microcrystalline cellulose (MCC) was carried out using published procedure of Ismail et al, [19]. Acid hydrolysis process of MCC was conducted with several concentrations of sulphuric acid (5%, 15%, and 25%).…”
Section: Preparation Of Microcrystalline Cellulosementioning
confidence: 99%
“…Out of 101.02 metric tonnes (MT) of processed oil palm empty fruit bunch fibre (OPEFB), the total oil palm biomass residues (dry weight basis) from replanting, pruning, and milling activities in Malaysia were projected to be 51. 19 MT in 2017 [4]. In addition to extractives in the cell wall, OPEFB is a lignocellulosic residue that contains 50% cellulose, 25% hemicellulose, and 20% lignin [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, Haafiz et al [43] reported that acid hydrolysis using 2.5 N HCl at 105 °C, followed by washing using 5% diluted ammonium hydroxide (NH4OH) produced rough, compact, and regular spherical MCC particles. The high crystallinity index proved that acid hydrolysis did not alter the crystal structure, hence the MCC had good thermal stability and high potential to be used as good reinforcing material in polymeric materials [44]. Apart from that, Ismail et al [44] reported that the MCC extracted from EFB using 5-25% H2SO4 under pressurized steam for 1 h showed maximal thermal durability which can be used as the nanocomposites.…”
Section: Acid or Alkali Extraction Of Hemicellulose And Cellulosementioning
confidence: 99%
“…The high crystallinity index proved that acid hydrolysis did not alter the crystal structure, hence the MCC had good thermal stability and high potential to be used as good reinforcing material in polymeric materials [44]. Apart from that, Ismail et al [44] reported that the MCC extracted from EFB using 5-25% H2SO4 under pressurized steam for 1 h showed maximal thermal durability which can be used as the nanocomposites. In contrast, Owolabi et al [45] studied the influence of alkaline hydrogen peroxide (AHP) concentration on the pre-treatment process of OPF before bleaching with acidified NaClO2 and acid hydrolysis using HCl.…”
Section: Acid or Alkali Extraction Of Hemicellulose And Cellulosementioning
confidence: 99%